2008
DOI: 10.1080/13651820801992625
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of cholangiocarcinoma

Abstract: Photodynamic therapy (PDT) is a local photochemical tumor treatment that consists of a photosensitizing agent in combination with laser irradiation of a distinct wavelength. In some case reports and small non-randomized pilot studies, PDT has proved feasible in patients with hilar bile duct cancer. Those studies showed an astonishing long survival time of the treated patients. In the yet published two randomized controlled studies, PDT showed a significant extension of survival compared to sole bile duct stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…[2][3][4][5] Remarkably, PDT treatment induces a powerful anti-tumor immunological response. 6 In two randomized controlled trials, PDT provided a longer survival. 4,5 PDT treatment benefits have been reported for treating the targeted area in BDC patients who are receiving chemotherapy or adjuvant chemotherapy after surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Remarkably, PDT treatment induces a powerful anti-tumor immunological response. 6 In two randomized controlled trials, PDT provided a longer survival. 4,5 PDT treatment benefits have been reported for treating the targeted area in BDC patients who are receiving chemotherapy or adjuvant chemotherapy after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…9 The first clinically approved photosensitizer, porfimer sodium (Photofrin ® ), is a hematoporphyrin derivative and has a very powerful cytocidal effect in BDC. [1][2][3][4][5][6][7][8] However, the anti-tumor effect was limited to the shallow bile duct wall because the 630 nm laser used in treatment had a low permeability. 10 Furthermore, the long period of skin photosensitivity required the patients to be kept away from strong sunlight for several weeks following the drug administration.…”
Section: Introductionmentioning
confidence: 99%
“…In two randomized controlled trials, PDT provided longer survival than bile duct stenting alone [6, 7]. A possible explanation for the improved survival is the powerful anti‐tumor immunological response induced by PDT [8]. Our group has also reported the benefits of PDT treatment in bile duct carcinoma as chemotherapy or adjuvant chemotherapy after surgery for local control [9].…”
Section: Introductionmentioning
confidence: 99%
“…Three recent reviews that analyzed the contribution of photodynamic therapy to the treatment of cholangiocarcinoma all confirmed these data. 11,42,43 In 2007, Prasad et al 44 found that patients with unresectable cholangiocarcinoma without a visible mass benefited from early treatment with PDT. They described a technique for photodynamic therapy using percutaneous biliary access.…”
Section: Review Of the Literaturementioning
confidence: 99%